Yeast glycosylation mutants are sensitive to aminoglycosides. - Dean, N (1995)
Aminoglycosides are a therapeutically important class of antibiotics that inhibit bacterial protein synthesis and a number of viral and eukaryotic functions by blocking RNA-protein interactions. Vanadate-resistant Saccharomyces cerevisiae mutants with defects in Golgi-specific glycosylation processes exhibit growth sensitivity to hygromycin B, an aminoglycoside [Ballou, L., Hitzeman, R. A., Lewis, M. S. & Ballou, C. E. (1991) Proc. Natl. Acad. Sci. USA 88, 3209-3212]. Here, evidence is presented that glycosylation is, in and of itself, a key factor mediating aminoglycoside sensitivity in yeast. Examination of mutants with a wide range of glycosylation abnormalities reveals that all are sensitive to aminoglycosides. This effect is specific to aminoglycosides and not merely a consequence of increased permeability of the yeast mutants to drugs. Furthermore, inhibition of glycosylation in wild-type cells leads to a marked increase in their sensitivity to aminoglycosides. These results establish that a defect in glycosylation is sufficient to render yeast cells susceptible to these clinically important drugs. Further, they suggest that a molecule which prevents the uptake or mediates removal of aminoglycosides requires glycosylation for its activity. Perhaps more importantly, this finding on drug sensitivity provides the most powerful screen to date to identify mutants and thereby to isolate genes involved in all aspects of N-linked glycosylation.